МЕЖДУНАРОДНЫЙ ОПЫТ ИННОВАЦИОННОГО ПРОЦЕССА МОДЕРНИЗАЦИИ ЭКОНОМИКИ ХИМИЧЕСКОЙ ПРОМЫШЛЕННОСТИ И ЕЁ ЭФФЕКТИВНОГО ИСПОЛЬЗОВАНИЯ В УЗБЕКИСТАНЕ (Scientific journal of the Fergana State University, 2023)
This article expounds the opinions and points of view found the reflection in relation to the prospect of increase of efficiency of the use, to continue joint useful relations the nearby states, yet more to develop petrochemical industry, on the basis of modernisation and innovative development of economy of chemical industry